Dimension of bilingualism (Journal of Universal Science Research, 2023)
As the great uzbek writer Alisher Navoi said: " Knowing a language- knowing a nation" and without any doubt, it is true. It is an indisputable fact,being able to speak and comprehend different languages gives a good many opportunities to have a bright future. This article renders the varities of bilingualism, manifests its role in society, also emphasizes its importance